1978
DOI: 10.1002/jcp.1040960310
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian cells in culture. II. Isolation of drug‐resistant variants and an asparagine‐independent variant

Abstract: With L-15 as the base medium, drug-resistant variants were isolated from two amphibian tissue culture strains: the Xenopus laevis A8 diploid cell line and the ICR 2A cell line of Rana pipiens. Four different classes of variants were obtained: (1) A8 cells resistant to chloramphenicol, an inhibitor of mitochondrial protein synthesis; (2) A8 cells resistant to ouabain, an inhibitor of the Na+/K+-activated ATPase of the plasma membrane;(3) ICR 2A cells resistant to low (20 microgram/ml) and high (300 microgram/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Although t h e field of genetic toxicology had its origins in studies on submammalian species [Brusick, 19801, mammalian and microbial species have become the mainstay of the short-term i n vitro mutagenicity tests that have been extensively developed and widely used to measure t h e mutagenic potential of a wide range of agents. Promi-nent among these are the Salmonella mutagen assay developed by Ames et a1 [1975], tests to detect chromosomal macrolesions such as sister chromatid exchange (SCE) [Latt, 1974;Stetka and Wolff, 1976a,b;Latt et al, 1977;Kligerman, 19791, micronucleus formation [Schmid, 1976;Maier and Schmid, 19761, and chromosomal aberrations [Ziemba-Zoltowska et al, 1980;Edwards et al, 1980;Tsuda, 1981;van Kesterenvan Leeuwen and Natarajan, 19801, as well as tests to detect microlesions such as DNA repair [Lieberman et al, 1971a,b;Viceps-Madore and Mezger-Freed, 19781 and direct cellular mutagenesis [Mankovitz et al, 1974;Arlett et al, 1975;Chinchar and Sinclair, 1978;Jacobs and DeMars, 19781. Since each procedure has its advantages and weak points, it has been suggested that a battery of tests be used to evaluate the mutagenic potential of substances [Nichols et al, 1977;Sobels, 19771. Since chromosomes can be examined in any living system that is undergoing mitosis or meiosis, this type of procedure can be used with embryos, regenerating tissue, lymphocytes, or cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…Although t h e field of genetic toxicology had its origins in studies on submammalian species [Brusick, 19801, mammalian and microbial species have become the mainstay of the short-term i n vitro mutagenicity tests that have been extensively developed and widely used to measure t h e mutagenic potential of a wide range of agents. Promi-nent among these are the Salmonella mutagen assay developed by Ames et a1 [1975], tests to detect chromosomal macrolesions such as sister chromatid exchange (SCE) [Latt, 1974;Stetka and Wolff, 1976a,b;Latt et al, 1977;Kligerman, 19791, micronucleus formation [Schmid, 1976;Maier and Schmid, 19761, and chromosomal aberrations [Ziemba-Zoltowska et al, 1980;Edwards et al, 1980;Tsuda, 1981;van Kesterenvan Leeuwen and Natarajan, 19801, as well as tests to detect microlesions such as DNA repair [Lieberman et al, 1971a,b;Viceps-Madore and Mezger-Freed, 19781 and direct cellular mutagenesis [Mankovitz et al, 1974;Arlett et al, 1975;Chinchar and Sinclair, 1978;Jacobs and DeMars, 19781. Since each procedure has its advantages and weak points, it has been suggested that a battery of tests be used to evaluate the mutagenic potential of substances [Nichols et al, 1977;Sobels, 19771. Since chromosomes can be examined in any living system that is undergoing mitosis or meiosis, this type of procedure can be used with embryos, regenerating tissue, lymphocytes, or cell culture.…”
Section: Introductionmentioning
confidence: 99%